IR and AR Implementation on Billboards / Alvein Dhiwaul Haq - Haq, Alvein Dhiwaul (2022)
With the application of technology to billboards in public places it will increase the desire of consumers because of creativity in promotion. In addition, it will be main attraction in public place which will make business products to be well promoted.